The Effect Of Brand Image And Electronic Word Of Mouth In Social Media Instagram Toward On Purchasing Decision Of Xiaomi Smartphone - Dias Wahyu Ramdani; Krishna Kusumahadi (Universitas Trunodjoyo Madura, 2023)
This study aims to seeing how big the relationship and the role that occurs between the brand image and electronic word of mouth in social media instagram toward on purchasing decisions of Xiaomi Smartphone. In this study used descriptive and causal research methods.The research method used in this study is a quantitative method. , there are two main variables that are the focus of this research. The brand image and electronic word of mouth variables are independent variables, hereinafter referred to as the independent variable (X), which is a type of variable that explains or influences other variables. Meanwhile, the purchase decision variable is the dependent variable or dependent variable (Y), which is a type of variable that is explained or influenced by the independent variable. The results of hypothesis testing can be concluded that brand image has a positive effect on the purchase decision variable and based on descriptive analysis, the average brand image variable is 83.88% so that it can be said to be in the